ANALISIS TINGKAT PENGETAHUAN TAKTIK DAN STRATEGI FUTSAL PADA PEMAIN EKSTRAKURIKULER FUTSAL SMA - Gusfi , Muhammad; Munar, Hendri; Yusradinafi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of knowledge of tactics and strategies possessed by futsal extracurricular players at SMAN 1 Muaro Jambi. The problem addressed in this study is the lack of clear information regarding the level of knowledge of tactics and strategies among these players. In futsal, tactics and strategies are essential aspects that influence game effectiveness, teamwork, and success in achieving victory. However, in practice, there are still players who lack understanding in applying attacking and defensive tactics, as well as game strategies appropriate to match situations. This condition can lead to poor decision-making on the field, lack of coordination among players, and suboptimal team performance patterns. The method used in this research is a descriptive quantitative approach. The population consisted of 30 players, with a sample of 24 players selected using purposive sampling based on specific criteria. The research instrument was a knowledge test in the form of a questionnaire consisting of 47 items. Data analysis was conducted descriptively using mean calculations and percentage categories. The results showed that the average score was 29.88, with a maximum score of 41 and a minimum of 13, and a standard deviation of 10.006. The category distribution indicated that most players were in the high category at 41.7%. In addition, 16.7% were in the very high category, 25.0% in the moderate category, 16.7% in the low category, and none were in the very low category. Therefore, it can be concluded that the players' level of knowledge is generally in the high category.